Human Scavenger Receptor A1-Mediated Inflammatory Response to Silica Particle Exposure Is Size Specific - Nishijima, Nobuo; Hirai, Toshiro; Misato, Kazuki; Aoyama, Michihiko; Kuroda, Etsushi; Ishii, Ken J.; Higashisaka, Kazuma; Yoshioka, Yasuo; Tsutsumi, Yasuo (Frontiers in Immunology, 2017)
The application of nanotechnology in the healthcare setting has many potential benefits; however, our understanding of the interactions between nanoparticles and our immune system remains incomplete. Although many of the biological effects of nanoparticles are negatively correlated with particle size, some are clearly size-specific and the mechanisms underlying these size-specific biological effects remain unknown. Here, we examined the pro-inflammatory effects of silica particles in THP-1 cells with respect to particle size; a large overall size range with narrow intervals between particle diameters (particle diameter: 10, 30, 50, 70, 100, 300, and 1000 nm) was used. Secretion of the pro-inflammatory cytokines interleukin (IL)-1beta and tumor necrosis factor (TNF)-alpha induced by exposure to the silica particles had a bell-shaped distribution where the maximal secretion was induced by silica nanoparticles with a diameter of 50 nm and particles with smaller or larger diameters had progressively less effect. We found that blockade of IL-1beta secretion markedly inhibited TNF-alpha secretion, suggesting that IL-1beta is upstream of TNF-alpha in the inflammatory cascade induced by exposure to silica particles, and that the induction of IL-1beta secretion was dependent on both the NLRP3 inflammasome and on uptake of the silica particles into the cells via endocytosis. However, a quantitative analysis of silica particle uptake showed that IL-1beta secretion was not correlated with the amount of silica particles taken up by the cells. Further investigation revealed that the induction of IL-1beta secretion and uptake of silica nanoparticles with diameters of 50 or 100 nm, but not of 10 or 1000 nm, was dependent on scavenger receptor A1. In addition, of the silica particles examined, only those with a diameter of 50 nm induced strong IL-1beta secretion via activation of Mer receptor tyrosine kinase, a signal mediator of scavenger receptor A1. Together, our results suggest that the scavenger receptor A1-mediated pro-inflammatory response is dependent on ligand size and that both scavenger receptor A1-mediated endocytosis and receptor-mediated signaling are required to produce the maximal pro-inflammatory response to exposure to silica particles.